EVALUATION OF CYTOTOXIC AND GENOTOXIC EFFECTS OF ZERUMBONE ON COLON ADENOCARCINOMA COLO205 CELLS AND HUMAN LYMPHOCYTES - Thiyam, Rima; Narasu, Mangamoori Lakshmi (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: The objective of the present study was to investigate the growth inhibitory effect, apoptosis initiation and genotoxic effect of zerumbone (ZER), a phytochemical and cisplatin, a chemotherapeutic drug on human colorectal cancer cell line COLO205 and normal human lymphocytes. Methods: The antiproliferative activity of ZER and cisplatin (positive control) on COLO205 cells and lymphocytes was analysed by 3( 4, 5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide (MTT) assay. Morphological analysis of the cells was studied by using inverted phase contrast microscope. Propidium iodide staining method was used to observe the apoptotic morphological changes in the treated cells. Finally comet assay was conducted to observe the extent of DNA damage induced by ZER and cisplatin on COLO205 and lymphocytes. Results: ZER and cisplatin exhibited growth inhibition in a dose and time dependent manner against COLO205 with no considerable effect on lymphocytes. The IC50 values of ZER on COLO205 for 24h, 48h and 72h were 19 Âµg/ml, 10 Âµg/ml and 5 Âµg/ml. Comparatively the IC50 values of cisplatin on COLO205 for 24h, 48h and 72h were 38 Âµg/ml, 24 Âµg/ml and 15 Âµg/ml.Â Morphological changes such as cell shrinkage, membrane blebbing and nuclear condensation were observed in COLO205 while no significant change was observed in lymphocytes. Fluorescence imaging studies confirmed apoptotic cell death in treated COLO205 cells while no significant cell death was observed in treated lymphocytes. Comet assay revealed significant DNA damage in treated COLO205 cells. Conclusion: The present study demonstrated the cytotoxic and genotoxic effect of ZER and cisplatin on COLO205 cells. These drugs showed no significant effect on lymphocytes.